KRONİK BÖBREK YETMEZLİĞİ TANILI HASTALARDA SERUM ALARİN SEVİYELERİNİN ARAŞTIRILMASI - TOPTAL, SEDA (Fırat Üniveristesi, 2017)
Kronik böbrek yetmezliği (KBY) böbrek fonksiyonlarında progresif kötüleşme ile birlikte birçok klinik anormalliği tarif eder. Kronik böbrek yetmezliği birçok sistemik hastalık ile sonuçlanır. KBY'ın şiddeti glomerüler filtrasyon hızındaki azalmaya göre derecelendirilir. Kronik böbrek yetmezliği giderek sıklığı artmakta olan bir hastalıktır. Yapılan çalışmalar sonucunda Türkiye'de her 6-7 kişiden birinde böbrek çeşitli aşamalarda böbrek hasarının olduğunu göstermektedir. Alarin ilk kez 2006'da insan nöroblastik tümörlerinin gangliosit hücrelerinden elde edilen oroksijenik bir nöropeptiddir. Çalışmamız farklı evrelerde olan 90 KBY hastası ve 30 kişiden oluşan sağlıklı kontrol grubu üzerinde yapılmıştır. Verilerin analizinde Kruskal Wallis testi, Mann Whitney-U testi, Spearman Korelasyon testi kulanılmıştır. Verilerin analizinde SPSS 22 paket programı kullanılmıştır. Anlamlılık değeri p? 0.05 olarak alınmıştır. Bütün hastaların ve kontrol grubunun alarin değerlerine bakıldığında hasta grubunun alarin değerleri kontrol grubundan yüksek ve istatistiksel açıdan anlamlı olarak bulunmuştur (p=0.018). Hasta grubunun GFR değerlerine göre yapılan evreleme alt grupları ile kontrol grubunun alarin değerleri istatistiksel açıdan anlamlı derecede farklıdır (p=0.014). Alt gruplara bakıldığında istatistiksel farkın Evre 5 hastalar ve kontrol grubundan kaynaklandığı görülmektedir (p=0.007). Hasta evrelerine göre bakılan alarin değerleri ile hasta evresi arasında pozitif yönde ve anlamlı korelasyon bulunmuştur. Korelasyon katsayısı r= 0.217, p=0.017 olarak bulunmuştur. Demografik özellikler açısından bakıldığında anlamlı bir fark bulunamamıştır. Sonuç olarak kronik böbrek yetmezliğinin evresi arttıkça ve GFR değeri düştükçe kan alarin düzeylerinin arttığı görülmüştür. Anahtar Kelimeler: Kronik böbrek yetmezliği, Alarin

Chronic Kidney Disease (CKD) refers to many clinical anomalies together with progressive deterioration in kidney functions. Chronic Kidney Failure results in many systemic diseases. CKD is assessed according to the decrease in the filtration speed of glomerular filtration. The frequency of Chronic Kidney Disease is increasing with each passing day. It has been reported in previously conducted studies that there are kidney damages at various levels in one out of every 6-7 people in Turkey. Alarin is an anorexigenic neuropeptide obtained from the ganglioside cells in human neuroblastic tumors, and was first defined in 2006. Our study was conducted on 90 CKD Patients at various stages of the disease and 30 Control Group Patients. In the analysis of the data, the Kruskal Wallis Test, Mann Whitney-U Test, and the Spearman Correlation Test were used. The SPSS 22 Package Program was also utilized in the analyses of the data. The significance level was taken as p? 0.05. When the Alarin values of the Patients and the Control Group were examined, it was determined that the Alarin values of the Patient Group were higher than those of the Control Group at a statistically significant level (p=0.018). In the staging that was made according to the GFR values of the Patient Group, it was determined that the Alarin levels of the sub-groups and the Control Group were different from each other at statistically significant level (p=0.014). When the sub-groups were examined, it was determined that the statistical difference stemmed from the Stage 5 patients and the Control Group (p=0.007). A positive and significant correlation was detected between the Alarin values, which were examined according to the stages of the patients, and the stage of the disease. The correlation coefficient was found to be r=0.217, p=0.017. In terms of demographical properties, no significant differences were found between the groups. As a conclusion, it was determined that as the stage of the Chronic Kidney Failure increase, and the GFR value decrease, the Alarin levels increase in the blood. Keywords: Chronic Kidney Disease, Alarin
Serum alarin level analysis in patients with chronic kidney disease
Keywords: Nefroloji